2021
DOI: 10.37013/jf.v10i1.117
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Ekstrak Alpinia galanga L Terhadap Produksi Biofilm pada Escherichia coli

Abstract: Escherichia coli merupakan bakteri Gram negatif berbentuk batang, mampu menyebabkan infeksi di beberapa bagian tubuh, dan ditemukan telah resisten terhadap berbagai antibiotic, salah satu factor penyebabnya adalah kemampuannya membentuk biofilm pada jaringan. Alpinia gallanga L memiliki kemampuan menghambat pembentukan biofilm terhadap beberapa bakteri. Tujuan Penelitian ini adalah untuk mengetahui kemampuan ekstrak Alpinia galangal L dalam menghambat produksi biofilm Escherichia coli. Penelitian ini di awali … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The results showed that the higher the concentration of basil leaf extract, the greater the inhibition of biofilm formation in Staphylococcus aureus in vitro, with minimal biofilm inhibition at a concentration of 30%. Minimum concentration differences are possible because there are differences in compound content and the extraction process of the materials used [15][16][17][18][19][20].…”
mentioning
confidence: 99%
“…The results showed that the higher the concentration of basil leaf extract, the greater the inhibition of biofilm formation in Staphylococcus aureus in vitro, with minimal biofilm inhibition at a concentration of 30%. Minimum concentration differences are possible because there are differences in compound content and the extraction process of the materials used [15][16][17][18][19][20].…”
mentioning
confidence: 99%